Lysippe nikiti sp. nov. (Polychaeta, Terebellomorpha) from the deep Pacific and Indian Oceans with an amendment to the generic diagnosis of Lysippe - Jirkov, Igor A. (Zootaxa, 2016)
Lysippe nikiti n. sp. is described from abyssal depths in the North Pacific and Indian Oceans. It differs from other species of the genus in that it has 14 thoracic uncinigers, ten abdominal uncinigers and three pairs of branchiae. The generic diagnosis is emended to include the newly described fully retractable nuchal organs of the type species L. labiata and details of the position of the nephridiopores. The validity of Samytha is discussed and it is proposed that this genus be treated as junior synonym of Lysippe. Of the 22 species described as Lysippe or its junior synonyms, eight: L. agulhasensis, L. capensis, L. vanelli—type species of Eclysippe, Samytha bioculata—type species of Mooresamytha, S. (?) heterobranchia, S. oculata, S. pallescens—type species of Glyphanostomum and S. (?) speculatrix—have been or should, for reasons discussed here, be transferred to other genera. Neither the original description nor later redescriptions allow differentiation of Samytha californiensis from L. gurjanovae. Thus Lysippe currently includes 13 valid species: L. annectens—type species of Paralysippe, L. annenkovae, L. caeca, L. fragilis—type species of Lysippides, L. gurjanovae, L. hesslei, L. labiata, L. mexicana—type species of Pseudampharete, L. nikiti, L. nipponica, L. sexcirrata, L. storchi and L. trichobranchia.